Assessing Road Conditions for Driving Safety of Hazardous Materials Transport - Wang, Y.; Liu, H. J.; Li, K. R.; Liu, C. L.; Wang, L.; Li, Z.; Xie, Helix; Zhou, Ning; Zeng, Yiping; Wang, Yan; Zheng, Yihu; Wang, Qihui; et al. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Ensuring the safety operation of hazardous materials transport is critical. Many previous works have reported various method to promote safety, while in this work, we identified and explored an overlooked aspect that affect the safety -- the real-time road conditions. For example, the slippery wet road or road with holes cause accidents for hazardous materials transport. Therefore, we argue that it is necessary to monitor the road conditions in real-time, and computer vision algorithms can make it possible. The advances in computer vision techniques shed light on the realm of road condition assessment. We reviewed and compared existing algorithms in this work. We also listed the existing road condition datasets and provided insights into how to apply the monitoring process with the safety framework of hazardous material transport.
Keywords: Algorithm design; Hazardous material transportation; Road condition; Safety sciences